A case‐control study: The association of serum paraoxonase 1 activity and concentration with the development of type 2 diabetes mellitus. Issue 3 (14th December 2017) - Crow, J. Allen; Meek, Edward C.; Wills, Robert W.; Chambers, Janice E.
Abstract: Background: A longitudinal study assessed serum paraoxonase 1 (PON1) activity and concentration as affected by age and as associated with the development of type 2 diabetes (T2D). PON1's recently established physiological function is the hydrolysis of lipolactones in oxidized LDL particles. Methods: Serum samples and clinical data collected and stored at different time points over a 20‐year interval in the Air Force Health Study were analysed. PON1 activity and concentration and C‐reactive protein concentration in samples from the same individuals 20 years apart were compared using a paired t test ( n  = 159). A case‐control study design and multivariable logistic regression analysis assessed the association of PON1's activity and concentration with the subsequent development of T2D ( n  = 222 and α = 0.10). Results: No difference with age was found in PON1 activity assessed using 3 substrates, paraoxon ( P  = 0.897), phenyl acetate ( P  = 0.994), and dihydrocoumarin ( P  = 0.505), or PON1 serum concentration ( P  = 0.357). C‐reactive protein concentration increased 0.7 mg/L ( P  = 0.004) over the 20‐year interval. Lower PON1 activity assayed with phenyl acetate ( P  = 0.015, OR = 1.25 per 1000 U/L decrease) was associated with an increased risk of developing T2D as was a lower PON1 serum concentration ( P  = 0.004, OR = 1.72 per 2 μmol/L decrease). PON1 activity assayed with paraoxon ( P  = 0.681) or dihydrocoumarin ( P  = 0.136) was not associated with the development of T2D. Conclusions: Lower PON1 activity and concentration were associated with an increased risk of developing T2D when adjusted for many of the common risk markers for T2D previously identified. Thus, PON1 may have merit as a biomarker for the development of T2D.